Reconstitution of Organismal Liver Clock Function Requires Light. (September 2019) - Miyake, Takahito; Doi, Masao
Abstract : Recently Koronowski et al . ( Cell, 2019) showed that reconstitution of the liver circadian clock in otherwise genetically arrhythmic mice revives the daily program of the nicotinamide adenine dinucleotide salvage pathway and glycogenesis in vivo . This liver-autonomous metabolic cycling cannot be sustained under constant darkness, revealing the importance of the daily light cycle to restore liver function.